Monitoring the presence of lard in virgin coconut oil (VCO) using Fourier transform infrared (FTIR) spectroscopy for halal authentication study - Rohman, Abdul; Che Man, Yaakob; Ismail, Amin; Hashim, Puziah (Halal Products Research Institute, Universiti Putra Malaysia, 2009)
This study highlights the application of Fourier transform infrared (FTIR) spectroscopy combined with chemometrics to analyze the presence of lard in virgin coconut oil (VCO). The spectral bands associated with VCO, lard, and its blends of VCO and lard with different concentrations of lard were scanned, interpreted, and identified.Discriminant analysis and partial least square (PLS) were used for qualitative and quantitative analyses, respectively. In order to check the validity of PLS model, the calibration model obtained was cross validated using “leave one out” method. The results showed that PLS able to predict the lard contents in VCO with equation y = 0.999x + 0.006, for the relation between actual value of lard (x) and FTIR predicted value (y) with coefficient of determination (R2) of 0.999 at frequency regions of 1120 – 950 cm-1.Furthermore, DA was successfully exploited for classification of VCO and that adulterated with lard.